2020
DOI: 10.3390/sym12081246
|View full text |Cite
|
Sign up to set email alerts
|

Research on Stress Characteristics of Segment Structure during the Construction of the Large-Diameter Shield Tunnel and Cross-Passage

Abstract: With the intensive development of China’s high-speed railway network and intercity railway network, the construction of the large-diameter shield tunnels and cross-passages is gradually increasing. The construction of large diameter shield tunnels and the excavation of cross-passages puts forward higher requirements for the stability and safety of segment structure. Based on the Wangjing tunnel project, this paper studies the segment displacement and mechanical response of the shield tunnel with a diameter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…(4) Structural stress. Previous studies have demonstrated that the influence of the opening on the mainline tunnel stress is concentrated at the opening position and 1-2 rings nearby [12,17]. Considering the symmetry, for each opening, three couples of strain gauges (one inside and one outside) are arranged longitudinally along the tunnel, to analyze the stress concentration degree and influence range, as shown in Figure 6a.…”
Section: Monitoring Schemementioning
confidence: 99%
See 3 more Smart Citations
“…(4) Structural stress. Previous studies have demonstrated that the influence of the opening on the mainline tunnel stress is concentrated at the opening position and 1-2 rings nearby [12,17]. Considering the symmetry, for each opening, three couples of strain gauges (one inside and one outside) are arranged longitudinally along the tunnel, to analyze the stress concentration degree and influence range, as shown in Figure 6a.…”
Section: Monitoring Schemementioning
confidence: 99%
“…The research methods to investigate the mechanical characteristics, e.g., stress state, deformation pattern of shield tunnels include theoretical analysis [13][14][15], numerical simulations [1,2,16,17], field monitoring [2][3][4][5], and model tests [18][19][20][21]. The combination of the cross passages and main tunnels is a complex three-dimensional structure, which is unrealistic to utilize classical theoretical methods such as beam-spring models or homogeneous ring models to perform analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, many studies have focused on the tunnel structure and surrounding rock failure. Tan et al based on the Wangjing tunnel project studied the segment displacement and mechanical response of the shield tunnel with a diameter of 10.5 m in the process of shield construction and cross-passage construction [4]. Fang et al and Zhang et al calculated the seepage-induced effective stress around a tunnel in an elastic half-plane [5][6][7].…”
Section: Introductionmentioning
confidence: 99%